Experimental evidence of heparanase, Hsp70 and NF-κB gene expression on the response of anti-inflammatory drugs in TNBS-induced colonic inflammation - Quaglio, Ana E. V. [UNESP]; Castilho, Anthony C. S. [UNESP]; Di Stasi, Luiz C. [UNESP] (Elsevier B. V., 2015)
Etiopathogenesis of inflammatory bowel disease is unclear and results from a complex interplay of genetic, microbial, environmental and immune factors. Elucidating the mechanisms that drive IBD depends on the detailed characterization of human inflammatory mediators in animal models. Therefore, we studied how intestinal inflammation affects heparanase, NF-κB and Hsp70 gene expression in rats, and if current intestinal anti-inflammatory drugs (sulphasalazine, prednisolone and azathioprine) act on these expressions. Moreover, we investigated the relationships among these genes with colonic cytokines levels (IL-1β, TNF-α, IL-6, INF-γ and IL-10) and oxidative stress that have fundamental role in IBD. Material and methods Macroscopic parameters (diarrhea, extension of lesion, colonic weight/length ratio and damage score), biochemical markers (myeloperoxidase and alkaline phosphatase activities, and glutathione, IL-1β, TNF-α, IL-6, INF-γ and IL-10 levels), gene expressions (heparanase, NF-κB and Hsp70), and microscopic evaluations (optic, electronic scanning and transmission microscopic) were performed in rats. Key findings Expression of heparanase, Hsp70 and NF-κB and oxidative stress were increased by inflammatory process and differentially modulated by sulphasalazine, prednisolone and azathioprine treatments. Protective effects of drugs were also related to differential modulation of cytokine changes induced by inflammatory process, showing different mechanisms to control inflammation. Significance Heparanase, NF-κB and Hsp70 gene expression participate in the inflammatory response induced by TNBS and represent pharmacological targets of the intestinal anti-inflammatory drugs. In addition, current drugs used to treat IBD (sulphasalazine, prednisolone and azathioprine) differentially modulate heparanase, NF-κB and Hsp70 gene expression, cytokine production and oxidative stress.
Keywords: Heparanase; Hsp70; Inflammatory bowel disease; Intestinal anti-inflammatory drugs; Intestinal inflammation; Nf-κb